Professional Guidelines for Tour Guides: The Practical State of Legal, Regulatory, And Methodological Support (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article highlights the historical and touristic significance of the monuments in Bukhara, a city that holds an important place in the field of guiding and tourism and attracts numerous visitors with its unique features. As a recommendation for guide services, the article provides methodological advice for trainee tour guides preparing to work in architectural monuments built in the second half of the 16th century under the leadership and funding of Abdullakhan II, who ruled the Bukhara Khanate during that period. These suggestions aim to support the organization of quality tourist services at such sites.